The Reminiscence of Terra Firma: penulisan ilmiah dan karya seni pameran / Siti Norhashimah Suman, Salwa Ayob, Zulkarnian Hassan ... [et al.] - Suman, Siti Norhashimah; Ayob, Salwa; Hassan, Zulkarnian; Ibrahim, Amirul Azani; Awang, Nor Nazida; Vermol, Verly Veto; Mohd Raffie, Mohd Shahrol Hanafi; Harun, Zahirah; Ali Yasin, Siti Maryam (UiTM Perak Press, 2021)
The Covid-19 Pandemic nowadays has put the ceramic art scene in a diversity of perspectives. It challenges ceramic artists to channel their physical artwork exhibitions into digital platforms. This pandemic also has changed the way of teaching and learning in the ceramic programme in Universiti Teknologi MARA (UiTM). Conventional methods of teaching and learning usually involve the face to face learning style, which nowadays requires some changes. This ceramic virtual art exhibition titled The Reminiscence of Terra Firma shows one of the examples of a new style of exhibition management in the ceramic course in UiTM. This virtual exhibition is one of the course’s components that students need to complete their project. The course in ceramic programme titled; Ceramic Exhibition Management, aims to educate students to manage an exhibition and to work in groups. It helps students to understand the exhibition event’s standard which is the knowledge that can be used for their employability in the future. This virtual exhibition is organized for the first time. Before the pandemic, the students managed the exhibition in the gallery, which was more exciting. Although this is the first time for the students to arrange the virtual exhibition, they managed to overcome their struggle to learn new things and performed well to realize this exhibition. All the lecturers who participated in this exhibition will always support the event. This virtual exhibition displays the selected best lecturers’ artworks and also features the lecturers’ expertise in their disciplines. Many artworks in this exhibition explore issues that are related to the artists’ interests and concerns which are developed in the artworks with aesthetic and artistic manners. The participation of the ceramic programme’s lecturers in The Reminiscence of Terra Firma virtual ceramic art exhibition proved that they are not just teaching the students with the theories and demonstration of ceramic forming, but they also have produced quality artworks. This exhibition is one of many ways to celebrate this academic expertise. Thus, congratulations to all exhibition committee members that have organised this event. Thank you to all lecturers who participated in this exhibition. “If you trust your materials and you trust your instincts, you will see things of beauty growing up in front of you, without you having anything to do with it.” (Micheal Cardew, English Studio Potter)